6 Initial palliation of tetralogy of fallot: comparison between BT shunt and RVOT stent. (28th April 2017) - Penford, G; Quandt, D; Ramchandani, B; Stickley, J; Mehta, C; Bhole, V; Stumper, O
Abstract : Background: Neonatal repair of symptomatic infants with Fallot-type(ToF) lesions remains the exception in the UK. Initial palliation can be achieved by creation of a BT shunt, or RVOT stenting. Aims: To compare the outcome of BTS and RVOT stent in the palliation of TOF. Methods: 10 year retrospective review of the outcome of 101 ToF patients who required initial palliation (RVOT stent n=60; BTS n=41) prior to complete repair. Detailed assessment of PA growth in patients with comparable underlying anatomy. Results: In the RVOT stent group vs the BT shunt group, there was a lower PICU admission rate (22% vs 100%) (p<0.001], a lower early mortality (1.7% vs 4.9%) [ns], a shorter initial hospital stay (7 vs 14 days) (p<0.004), and a shorter time to surgical repair (232 vs 428 days) (p<0.001). In terms of PA growth after palliation, the benefit of RVOT stenting versus mBTS was 0.599 z-score for the LPA and 0.749 z-score for the RPA. Rise in oxygen saturations was greater with RVOT stenting (p=0.012). There were 3 non-cardiac deaths in the RVOT stent group and none in the BTS group. There were no deaths after correction, and comparable bypass times and rate of transannular patching/conduit use. Overall mortality was comparable (8.4% vs 4.9%) (p=0.69). Conclusions: RVOT stenting is a safe and effective palliation in the initial treatment of infants with symptomatic Fallot-type lesions and promotes pulmonary artery growth.